2002
DOI: 10.1002/pen.11019
|View full text |Cite
|
Sign up to set email alerts
|

Shear stress nucleation in microcellular foaming process

Abstract: The effect of shear stress on the foaming process has been studied using the Foaming Process Simulator developed previously. The polymer samples were saturated with gas in the test chamber. A rotor was used to apply shear stress to the polymer samples. Foams were obtained by releasing the pressure quickly. Polystyrene. Hled and unfilled, was used as the material. The cell density was analyzed with a scanning electron microscope. It was found that the cell density was s - -cantly increased by introducing shear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 9 publications
(5 reference statements)
4
58
1
Order By: Relevance
“…Among the polymer foaming community, the discrepancy between the classical theory and experimental results is sometimes attributed to the intervening heterogeneous nucleation provided by filler solid surface and has led to the classical theory modifications by incorporating certain aspects specific to the polymer foaming process [9,[32][33][34]. Nanoparticles have been validated that undoubtedly serve with heterogeneous nucleation sites and their influence on the cell density has been qualitatively represented by the classical nucleation theory [32,34].…”
Section: Effects Of Eg Particle Sizementioning
confidence: 99%
“…Among the polymer foaming community, the discrepancy between the classical theory and experimental results is sometimes attributed to the intervening heterogeneous nucleation provided by filler solid surface and has led to the classical theory modifications by incorporating certain aspects specific to the polymer foaming process [9,[32][33][34]. Nanoparticles have been validated that undoubtedly serve with heterogeneous nucleation sites and their influence on the cell density has been qualitatively represented by the classical nucleation theory [32,34].…”
Section: Effects Of Eg Particle Sizementioning
confidence: 99%
“…Chen et al [51] have introduced shear in their study of bulk polymer foaming by constructing a chamber wherein a polymer/CO 2 solution is sheared for a specified duration and then foamed without shear. If the sheared material is confined, the oriented nucleation sites produce cells that are elongated along the direction of shear.…”
Section: Pore Cell Anisotropymentioning
confidence: 99%
“…Recently, a cell stretch model has been developed by Chen et al [3] to explain the shear stress nucleation. They concluded that the key issue with shear stress nucleation was the transformation of mechanical shear energy into surface energy.…”
Section: Introductionmentioning
confidence: 99%